2022
DOI: 10.3390/bios12050352
|View full text |Cite
|
Sign up to set email alerts
|

Fiber-Optic Distributed Sensing Network for Thermal Mapping of Gold Nanoparticles-Mediated Radiofrequency Ablation

Abstract: In this work, we report the design of an optical fiber distributed sensing network for the 2-dimensional (2D) in situ thermal mapping of advanced methods for radiofrequency thermal ablation. The sensing system is based on six high-scattering MgO-doped optical fibers, interleaved by a scattering-level spatial multiplexing approach that allows simultaneous detection of each fiber location, in a 40 × 20 mm grid (7.8 mm2 pixel size). Radiofrequency ablation (RFA) was performed on bovine phantom, using a pristine a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 60 publications
1
1
0
Order By: Relevance
“…Moreover, the agarose gel provided a similar heating trend for all trials with the minimal standard deviation values. This experimental analysis shows two important conclusions: (1) The use of agarose gel substantially increases the ablated surface, as the average values rise from 25–40 mm 2 without agarose to 56–70 mm 2 with agarose; (2) The agarose gel counters the heat-sink effect significantly, resulting in ablated areas that are even larger than in absence of blood vessels (55 mm 2 average as reported in [ 12 ]). This can be explained by the fact that the medical tube has a resistance of a few tens of kΩ, but when coated with agarose gel, the impedance significantly lowers and allows heat to pass through; in this case, since we used a higher RF power, we could also obtain larger ablated surfaces.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Moreover, the agarose gel provided a similar heating trend for all trials with the minimal standard deviation values. This experimental analysis shows two important conclusions: (1) The use of agarose gel substantially increases the ablated surface, as the average values rise from 25–40 mm 2 without agarose to 56–70 mm 2 with agarose; (2) The agarose gel counters the heat-sink effect significantly, resulting in ablated areas that are even larger than in absence of blood vessels (55 mm 2 average as reported in [ 12 ]). This can be explained by the fact that the medical tube has a resistance of a few tens of kΩ, but when coated with agarose gel, the impedance significantly lowers and allows heat to pass through; in this case, since we used a higher RF power, we could also obtain larger ablated surfaces.…”
Section: Discussionsupporting
confidence: 62%
“…RFA provides a treatment that combines the miniaturization of the applicator and its tip electrodes with the localization of the bio-heating process in the surrounding tissue [ 11 ], as well as allowing the ablation of large volumes. Recent studies, in addition, have shown how the use of gold [ 12 ] and silver [ 13 ] nanoparticles might significantly expand the treated area. For example, Ashikbayeva et al reported a 102% increase in the ablated surface area when using green-synthesized Ag nanoparticles in an agarose gel, and a 72% increase when using agarose only.…”
Section: Introductionmentioning
confidence: 99%